Efficiency of the Albanian banking system: Traditional approach and Stochastic Frontier Analysis - Suela Kristo (International Journal of Economic Sciences and Applied Research, 2013)
Efficiency issues become even more sensitive for post-communist European countries and for Albania as well, as their economies have created relatively new financial systems being currently of little experience, moreover when they become part of EU. Their survival requires them among others, to be as efficient as possible. The paper focuses on the dynamics of bank efficiency banking system as a whole and for each of the banks in particular. Firstly, the analysis is done through traditional indicators. These indicators clearly show a poor performance and decreased efficiency of Albanian banking system after year 2007. Then, is estimated the cost efficiency through Stochastic Frontier Approach (SFA). This efficiency estimation captures essentially the deviation that a bank has from the theoretical best-practice bank. Results show that in particular, the largest banks (which have the largest market share G3 group) seem to be more efficient than the smaller banks. However, the differences that they have on each other are much smaller than in the case of traditional indicators. Moreover, it is not clear the relationship between ROA or size of the bank with the cost efficiency.
Keywords: G21; G14; C33; 330; bank efficiency; Albanian banking system; SFA